«Dimostrare al di fuori» e «ravvivare al di dentro». La Scuola Orientale di Roma e il riordinamento degli studi orientali in Italia - Crisanti, Alice (Annali di Ca’ Foscari: Serie Orientale, 2022)
This paper aims to retrace a piece of the history of Oriental Studies in Rome and, more broadly, in Italy in the first years of the 20th century. Starting from unpublished documents, it chronicles the events related to the establishment of the Oriental School at the University of Rome (1904) and the subsequent reorganisation effort its professors – directed by I. Guidi – had hoped for. This attempt was the occasion for F.L. Pullé, in his role of member of the High Council for Public Education, to draw up a detailed report on Italian Oriental Studies which put forth a series of concrete proposals for a more general renewal of this field. In addition to allowing a better understanding of the history of Roman – and, more generally, Italian – Oriental Studies, the events recounted herein are emblematic of a broader effort, sustained by the same Orientalists since the mid-nineteenth century, to give a recognisable identity and a unitary orientation to a diverse group of disciplines.